Field Recording, Autoethnography, and the Entanglements of the Heard: Author’s Note and References - Sinha, Debashis (Performance Matters, 2023)
An audio essay considering the act of recording, of editing, of the moment and the ways in which they entangle with each other. A proposal of a methodology for listening to the story of the sound around and within us, through the practice of field recording and the myriad ways we might consider the archive, the preferences at play, and the processes we use to extract meaning in field recording practice.